A History of Concussion Does Not Lead to an Increase in Ocular Near Point of Convergence - van Donkelaar, Paul; Dierijck, Jill; Wright, Alexander; Smirl, Jonathan (International Journal of Sports Medicine, 2018)
Ocular near point of convergence (NPC) has been shown to be sensitive to the effects of concussion and subconcussive impacts. To determine if NPC is also sensitive to a previous history of concussion, male contact-sport athletes either with (n=26) or without (n=16) a history of at least one previous concussion had their NPC assessed. The results showed that participants with a history of concussion displayed NPC values (9.4±1.6 cm) indistinguishable from those with no history of concussion (8.4±2.1 cm, t-test, p=0.09). This was the case regardless of whether 1, 2, or 3 or more concussions had occurred and despite the fact participants with concussion (mean time since last concussion: 1136 days) suffered from an increased number and severity of symptoms as assessed with the SCAT 3 (3.6±2.2 vs. 2.13±1.89 symptoms, 6.1±4.1 vs. 3.19±2.99 severity, t-test, p<0.05). Taken together, these results imply that NPC may not be a suitable tool to assess the potential long-term effects of one or more concussions over a longer time frame. Future research using larger sample sizes is warranted to evaluate the potential dose-response relationship between number of prior concussions and NPC.
Keywords: concussion; near point of convergence; accommodation; visual function